KARAKTERISTIK MATA PELAJARAN FIQH IBADAH ( Menelisik Hasil Pembelajaran Fiqh Melalui Pengamalan Ibadah Siswa) - Tauhid, Moh (At-Tawazun, Jurnal Ekonomi Syariah, 2020)
Each learning activity will end with a learning outcome or so-called learning achievement. Learning achievement is a valuable material for students, namely to improve the ways of further learning. Until now the learning achievement is still used as a benchmark to determine the quality of students. Learning achievement is the abilities possessed by the students after he received his learning experience. The study of jurisprudence is useful to determine the attitude and wisdom in drawing conclusions and apply the rules of fiqih to the facts that exist so as not to cause unnecessary excesses due to the priority scale of its application. Do not behave ifrath, which is more than the limit and not also bertkap tafrith, which is less than the limit. Studying the science of fiqih is useful as a benchmark to behave in living life and life. By studying the science of jurisprudence, also we will know the rules in detail about the duties and responsibilities of man against his Lord and his obligations in social life. By studying the science of jurisprudence also we will know the command of Allah and the prohibition of Allah, halal, haram, which is void and which is fasid. The practice of worship, such as exercising thaharah well and rightly as an absolute requirement to be able to perform other worship such as the five-time prayer is something very urgent in the life of a Muslim. With the learning achievement of jurisprudence, of course the practice of worship the result is very maximum, because in fiqih discussed about the provisions of how humans perform worship as a form of servantship to Allah swt.